A donor–acceptor ligand boosting the performance of FA0.8Cs0.2PbBr3 nanocrystal light-emitting diodes. Issue 3 (12th January 2021) - Shen, Wei; Lu, Yao; Xia, Pengfei; Zhang, Wenzhu; Chen, Yanfeng; Wang, Wei; Wu, Yanan; Liu, Lihui; Chen, Shufen
Abstract : A donor–acceptor ligand, 3-amino-2-bromo-6-methoxypyridine (ABMeoPy), was introduced to boost the performance of perovskite light-emitting diodes (LEDs). Abstract : A donor–acceptor ligand, 3-amino-2-bromo-6-methoxypyridine (ABMeoPy), was introduced to passivate FA0.8 Cs0.2 PbBr3 nanocrystals (NCs) by a post-processing method. The donor–acceptor interaction can greatly enhance the coordination bond of pyridine-Pb 2+, and improve FA0.8 Cs0.2 PbBr3 NC performance with 95.99% photoluminescence quantum yield (PLQY), 6-month stability in solution, and 26% trap density decrease. In the light of ABMeoPy passivation of FA0.8 Cs0.2 PbBr3 NCs, the maximum luminance, the maximum current efficiency, and EQE of light-emitting diodes (LEDs) increased 69%, 110%, and 111%, respectively. The strategy of using D–A molecules to passivate perovskite NCs is quite simple and effective, which can be widely promoted in perovskite-based LEDs or solar cells.